Highly Selective Reduction of α, β‐Unsaturated Aldehydes and Ketones under Ambient Conditions using Tetraalkylphosphonium‐based Ionic Liquids. Issue 42 (21st September 2018) - Ralphs, Kathryn; McCourt, Éadaoin; Ormandy, Christopher; Carneiro de Souza, Thiago A.; Nockemann, Peter; Jacquemin, Johan; Manyar, Haresh G.
Abstract: An efficient and green protocol for highly selective reduction of α, β ‐unsaturated aldehydes and ketones at room temperature is described in a range of ionic liquids, in the absence of noble metal catalysts, by using NaBH4 as reducing agent. Most notably, using [P6, 6, 6, 14 ][N(CN)2 ] ionic liquid, in absence of organic solvent, within 10 min, 97% conversion of cinnamaldehyde was achieved with 100% selectivity towards cinnamyl alcohol. The ionic liquid was easily recycled without any noticeable decline in activity. The reduction protocol was further extended to a variety of α, β ‐unsaturated aldehydes and ketones. Abstract : A novel protocol for highly selective reduction of a range of α, β ‐unsaturated aldehydes and ketones at room‐temperature has been developed. In the absence of organic solvent, using [P6, 6, 6, 14 ][N(CN)2 ] ionic liquid, 100% selectivity to cinnamyl alcohol at 97% cinnamaldehyde conversion was achieved within 10 minutes.